Etika zmožnosti, priporočilni in pogovorni sistemi UI in doseganje dobrega življenja - Centa Strahovnik, Mateja (Bogoslovni vestnik, 2024)
This paper explores the link between capability ethics and artificial intelligence (AI). It introduces capability ethics as a framework for research and highlights the rapid growth of AI technology and its integration into everyday life. The paper focuses on two aspects: how AI contributes to the development of an individual's core capabilities and how capability ethics can be used to develop an ethics of AI, including an assessment of the risks and impacts of AI and suggestions for measures to limit or mitigate them.
Keywords: artificial intelligence (AI); capability approach; chatbots; dobro življenje; etika zmožnosti; good life; identiteta; identity; pogovorni sistemi; priporočilni sistemi; recommendation systems; umetna inteligenca (UI)